Hemoglobin concentration and blood shift during dry static apnea in elite breath hold divers - Kjeld, Thomas; Krag, Thomas O.; Brenøe, Anders; Møller, Ann Merete; Arendrup, Henrik Christian; Højberg, Jens; Fuglø, Dan; Hancke, Søren; Tolbod, Lars Poulsen; Gormsen, Lars Christian; Vissing, John; Hansen, Egon Godthaab (Frontiers in Physiology, 2024)
Elite breath-hold divers (BHD) enduring apneas of more than 5 min are characterized by tolerance to arterial blood oxygen levels of 4.3 kPa and low oxygen-consumption in their hearts and skeletal muscles, similar to adult seals. Adult seals possess an adaptive higher hemoglobin-concentration and Bohr effect than pups, and when sedated, adult seals demonstrate a blood shift from the spleen towards the brain, lungs, and heart during apnea. We hypothesized these observations to be similar in human BHD (n=11), and therefore we measured hemoglobin-and 2,3-biphosphoglycerate -concentrations in BHD and matched controls at rest, while myocardial mass, spleen and lower extremity volumes were assessed at rest and during apnea in BHD.After 4 min of apnea, left ventricular myocardial mass (LVMM) determined by 15 O-H2O-PET/CT (n = 6) and cardiac MRI (n=6),was unaltered compared to rest.During maximum apnea (~6 min), lower extremity volume assessed by DXA-scan revealed a ~268 ml decrease, and spleen volume, assessed by ultrasonography, decreased ~102 ml.Compared to age, BMI and V ̇O2max matched controls (n=11), BHD had similar spleen sizes and 2,3biphosphoglycerate -concentrations, but higher total hemoglobin-concentrations.1) Apnea training in BHD may increase hemoglobin concentration as an oxygen conserving adaption similar to diving mammals.2) The blood shift during dry apnea in BHD is 162% more from the lower extremities than from the spleen.3) In contrast to the previous theory of the blood shift demonstrated in sedated adult seals, blood shift is not towards the heart during dry apnea in humans.